Letter: improve survival! Place early pre‐emptive TIPSS in high‐risk variceal bleeders—Authors' reply. Issue 5 (14th August 2020) - Dunne, Philip D. J.; Sinha, Rohit; Stanley, Adrian J.; Lachlan, Niel; Ireland, Hamish; Shams, Aman; Kasthuri, Ram; Forrest, Ewan H.; Hayes, Peter C.
Abstract : LINKED CONTENT This article is linked to Dunne et al and García‐Pagán et al papers. To view these articles, visit https://doi.org/10.1111/apt.15797 and https://doi.org/10.1111/apt.15926